2007
DOI: 10.1007/s00253-006-0575-3
|View full text |Cite
|
Sign up to set email alerts
|

High activity of xylose reductase and xylitol dehydrogenase improves xylose fermentation by recombinant Saccharomyces cerevisiae

Abstract: Xylose fermentation performance was studied of a previously developed Saccharomyces cerevisiae strain TMB 3057, carrying high xylose reductase (XR) and xylitol dehydrogenase (XDH) activity, overexpressed non-oxidative pentose phosphate pathway (PPP) and deletion of the aldose reductase gene GRE3. The fermentation performance of TMB 3057 was significantly improved by increased ethanol production and reduced xylitol formation compared with the reference strain TMB 3001. The effects of the individual genetic modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
160
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(172 citation statements)
references
References 34 publications
9
160
0
1
Order By: Relevance
“…Reductive metabolism of acetate occurs during the solventogenic phase by some Clostridium species, where acetate can be converted to ethanol using surplus NADH generated during the acidogenic phase 24 . By contrast to the redox-neutral xylose isomerase (XI) pathway for converting xylose into xylulose 25,26 , we reason that the surplus NADH generated from xylose metabolism using the XR/XDH pathway could provide the reducing equivalent for acetate reduction. Conversely, reduction of acetate to ethanol could serve as an electron sink to alleviate the redox cofactor imbalance resulting from xylose fermentation (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Reductive metabolism of acetate occurs during the solventogenic phase by some Clostridium species, where acetate can be converted to ethanol using surplus NADH generated during the acidogenic phase 24 . By contrast to the redox-neutral xylose isomerase (XI) pathway for converting xylose into xylulose 25,26 , we reason that the surplus NADH generated from xylose metabolism using the XR/XDH pathway could provide the reducing equivalent for acetate reduction. Conversely, reduction of acetate to ethanol could serve as an electron sink to alleviate the redox cofactor imbalance resulting from xylose fermentation (Fig.…”
mentioning
confidence: 99%
“…1). Notably, XR-XDH-carrying strains have significantly higher xylose consumption rates, specific ethanol productivity and final ethanol concentration, when compared with otherwise isogenic XI-carrying strains, although XI strains achieve higher ethanol yields 26 . Therefore, here we aim to implement the acetate reduction pathway together with the XR-XDH pathway in S. cerevisiae.…”
mentioning
confidence: 99%
“…The ability to generate and convert fermentable sugars from lignocellulosic materials to ethanol in a cost-effective fashion is the central technological challenge to fully unlock its commercial potential (3). Unfortunately, fermentation of hydrolysates derived from pretreated lignocellulosic biomass is often preceded by washing (4), nutrient supplementation (5,6), and detoxification (7,8), which are very costly processes (9,10). The fermentability of a hydrolysate is strongly dependent on the feedstock pretreatment and strain selection.…”
mentioning
confidence: 99%
“…Thus, many studies attempted to optimize the expression levels of the genes coding for the XR/XDH pathway or to engineer XR and XDH proteins with balanced cofactor preferences to reduce xylitol accumulation and increase the ethanol yield (19,28,(54)(55)(56)(57)(58)(59)(60). While previous efforts to improve xylose fermentation mostly focused on manipulation of enzymatic reactions related to xylose metabolism, this study demonstrated an innovative approach that controls the carbon flux by accumulating the intermediate product (i.e., xylitol) inside the cell to facilitate the reaction toward the target direction.…”
Section: Discussionmentioning
confidence: 99%
“…Two types of xylose-assimilating pathways have been identified and used to engineer xylose-utilizing S. cerevisiae strains. One is the redox cofactor-dependent xylose reductase (XR)/xylitol dehydrogenase (XDH) pathway (8)(9)(10)(11)(12)(13)(14)(15), and the other is the redoxneutral xylose isomerase (XI) pathway (16)(17)(18)(19)(20)(21)(22)(23). Introduction of the XR/XDH pathway into S. cerevisiae by metabolic engineering approaches has been widely studied, but redox imbalance is a key problem, because XR can use both NADPH and NADH, while XDH uses NAD ϩ exclusively (6,24).…”
mentioning
confidence: 99%